2007
DOI: 10.1002/pen.20894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melt processing conditions on the morphology and properties of nylon 6 nanocomposites

Abstract: Nylon 6 (PA‐6) organoclay nanocomposites were prepared by melt processing using three different twin screw extruders (TSEs). The effect of mixing conditions, feed port location, residence time, and number of extrusion passes on the morphology and mechanical properties of the nanocomposites were examined. Wide‐angle X‐ray scattering, transmission electron microscopy (TEM), and mechanical property data are reported. Particle analyses were performed on the TEM images to quantitatively characterize the extent of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 36 publications
3
51
0
1
Order By: Relevance
“…This advantage could have a significant impact on alleviating concerns about the environmental impact of plastic packaging by reducing pack weight as well as the energy required to process and transport it. Despite the huge research interest in polymer-clay nanocomposites, studies on the processing of these materials have been largely confined to the effects of extrusion conditions (shear flow) on the melt processed polymer-clay structure and properties [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…This advantage could have a significant impact on alleviating concerns about the environmental impact of plastic packaging by reducing pack weight as well as the energy required to process and transport it. Despite the huge research interest in polymer-clay nanocomposites, studies on the processing of these materials have been largely confined to the effects of extrusion conditions (shear flow) on the melt processed polymer-clay structure and properties [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…PP/MMTs are produced using many technologies, and their applications include a range of manufacturing processes at a relatively low cost [1,2] . There is much evidence that supports melting processing as the preferred production method of PP/MMT for commercial use [3][4][5][6][7] . Additionally, the literature suggests that the exfoliation and the dispersion of nanoclays in polypropylene requires the exchange of the sodium cations that are present in the nanoclay layers with the organophilic cations (dimethyl, dihydrogenated tallow, and quaternary ammonium chloride), which alters the initial interlayer spacing and improves the interaction between the clay and the PP [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that it is important to use processing equipment that is flexible in design with the capability to control the residence time with dispersive and distributive mixing. Both the feed location and the order of feeding are also important considerations when designing the compounding process [4,11] . The screw configuration, the screw speed, the residence time, the feeder type, and the temperature of the melt process all have a large effect on the dispersion of the clay in the polymer matrix [22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in situ polymerization, melt compounding and a masterbatch method, and did not find any significant difference in structure and properties of polystyrene (PS) nanocomposites. On the other hand, Paul and co-workers [19][20][21] carried out a detailed study on polyamide 6 (PA6) nanocomposites using a single and three twin-screw extruders for processing and found a profound effect of conditions on the structure of the composites. Twin-screw extruders, longer residence time and medium shear resulted in larger extent of exfoliation than other conditions including high shear.…”
mentioning
confidence: 99%